PROFIL ASAM LEMAK RANTAI CABANG CAIRAN RUMEN YANG DISUPLEMENTASI LEGUMINOSA DALAM RANSUM BERBASIS INDEKS SINKRONISASI PROTEIN-ENERGI - Afduha Nurus Syamsi; Lastriana Waldi; Tri Puji Rahayu (Journal of Livestock Science and Production, 2018)
The experiment was aimed to assess the use of the legume and synchronization index of protein and energy (SPE) in the diet of dairy cattles on branch chain volatile fatty acids (BCVFA) profile. The research was applied in In vitro technique. The research was used a Completely Randomized Design (CRD), factorially pattern (2x3), the first factor was the two species of legume (Sesbania and Leucaena) and the second factor was the three levels of the SPE index (0.4, 0.5, and 0.6), there were 6 treatments combination and replicates 4 times each. The results showed interaction between legumes with SPE index was highly significant (P<0.01) upon iso butirat, but was nonsignificant (P>0,05) on iso valerat and valerat. Legume and SPE index respectively showed nonsignificant (P>0.05) on iso valerat and valerat. It can be concluded that Turi supplementation with high SPE index (0.6) gave the best effect on Branch Chain Volatile Fatty Acids (BCVFA) profile. Key words: Branch chain volatile fatty acids, Protein-energy synchronization index, LegumeThe experiment was aimed to assess the use of the legume and synchronization index of protein and energy (SPE) in the diet of dairy cattles on branch chain volatile fatty acids (BCVFA) profile. The research was applied in In vitro technique. The research was used a Completely Randomized Design (CRD), factorially pattern (2x3), the first factor was the two species of legume (Sesbania and Leucaena) and the second factor was the three levels of the SPE index (0.4, 0.5, and 0.6), there were 6 treatments combination and replicates 4 times each. The results showed interaction between legumes with SPE index was highly significant (P<0.01) upon iso butirat, but was nonsignificant (P>0,05) on iso valerat and valerat. Legume and SPE index respectively showed nonsignificant (P>0.05) on iso valerat and valerat. It can be concluded that Turi supplementation with high SPE index (0.6) gave the best effect on Branch Chain Volatile Fatty Acids (BCVFA) profile. Key words: Branch chain volatile fatty acids, Protein-energy synchronization index, Legume